Adherence in Youth With Multiple Sclerosis: A Qualitative Assessment of Habit Formation, Barriers, and Facilitators. (April 2019) - Yeh, E. Ann; Chiang, Nicole; Darshan, Bindia; Nejati, Nadine; Grover, Stephanie A.; Schwartz, Carolyn E.; Slater, Ruth; Finlayson, Marcia; ,
Rates of medication nonadherence in youth with multiple sclerosis (MS) range from 10% to 60%. Qualitative studies of adherence can provide insight into children's own perspectives about barriers and facilitators to their adherence and inform future interventions. This qualitative longitudinal descriptive study included children with MS ( n = 28) participating in a randomized controlled trial focused on medication adherence (clinicaltrials.gov : NCT02234713). Following established methods, three independent reviewers coded transcripts of motivational interviewing (MI) sessions (three interviews per subject, performed monthly over a 3-month period) for relevant themes. They were subsequently categorized using inductive content analysis. Youth described medication adherence as being dependent on the ability to build and maintain healthy habits related to medication use, including embodiment of these habits. Barriers and facilitators included remembering/forgetting, experiences with fatigue, and experiences with medication. These themes were maintained through the second and third interviews. Future research focus on barriers and facilitators to habit maintenance in this population.